Add Bilingualism to the Mix: L2 Proficiency Modulates the Effect of Cognitive Reserve Proxies on Executive Performance in Healthy Aging - Gallo, Federico; Kubiak, Joanna; Myachykov, Andriy (Frontiers in Psychology, 2022)
We investigated the contribution of bilingual experience to the development of cognitive reserve (CR) when compared with other, traditionally more researched, CR proxies, in a sample of cognitively healthy senior (60+) bilingual speakers. Participants performed in an online study where, in addition to a wide inventory of factors known to promote CR, we assessed several factors related to their second language (L2) use. In addition, participants’ inhibitory executive control was measured via the Flanker Task. We used Structural Equation Modeling to derive a latent composite measure of CR informed by traditional CR proxies (i.e., occupational complexity, marital status, current and retrospective socio-economic status, physical exercise, perceived positive support, maximal educational attainment, frequency of leisure activities and extent of social network). We examined whether bilingualism may act as a mediator of the effects of such proxies on cognitive performance therefore assessing the unique contribution of dual language use to CR. First, our analyses revealed facilitatory effects of both L2 age of acquisition and L2 proficiency on the executive performance. Second, our analyses confirmed the moderating role of bilingual experience on the relationship between other factors known to promote CR and cognitive integrity, revealing a strong contribution by bilingualism to CR development. Our findings provide further support to the notion that bilingualism plays an important role in mitigating cognitive decline and promoting successful aging.